(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Introduction : Spinal anaesthesia is the technique of choice for caesarian section. But post-spinal headache (PSH) is still a headache for the anaesthesiologist even after using modern spinocaine needles. Objective : This study was performed to compare the incidence of PSH between midline and lateral approach when caesarian sections were done by spinal anaesthesia. Methods : After ethical clearance this study was done in Chittagong Medical College Hospital. Two hundred pregnant women of American Society of Anesthesiologists (ASA) physical status I & II who underwent caesarian section were included and randomized into 2 groups. After informed consent spinal needle were inserted by midline approach in Group A patients and by lateral approach in Group B patients. After appearance of free flow of CSF 0.5% hyperbaric bupivacaine 10 mg was injected to each patient. PSH and other complications were evaluated. Results : Incidence of PSH was significantly higher in Group A patients. Conclusion : Lateral approach during spinal anaesthesia is better than midline approach in preventing PSH. J Bangladesh Coll Phys Surg 2017; 35(3): 123-127